Study of the behavior and resistance of right-angle truss shear connector for composite steel concrete beams. (15th February 2022) - Lima, Jerfson M.; Bezerra, Luciano M.; Bonilla, Jorge; Barbosa, Wallison C.S.
Highlights: Evaluation of an alternative shear connector for composite steel–concrete beams. Make popular, easy to use, a new low-cost and efficient connector for steel–concrete beams. A parametric study is carried out to evaluate the strength of the connector. An equation to determine the resistant capacity of the connector is proposed. The resistant capacity of this new connector is superior to that of the stud bold connector. Abstract: The Right-Angle Truss connector is a newly developed shear connector that features efficient structural behavior and low manufacturing and installation cost. However, for the application of this connector in composite steel–concrete beams, studies that evaluate its behavior in greater detail need to be developed. Thus, this study aims to evaluate the shear resistance of the Right-Angle Truss connector with the variation of parameters inherent to the connection of composite steel–concrete beams. For this, a non-linear finite element model, capable of simulating push-out tests with a Right-Angle Truss connector was developed. The numerical model was validated with experimental results. From a parametric study, the influence of the diameter of the bar that constitutes the connector and the strength of the concrete on the shear resistance of the Right-Angle Truss connector was evaluated. The application orientation of this connector which provides the greatest shear resistance was also studied. An equation to prescribe the shear resistance of the Right-Angle Truss connector was proposed.